Human Resource Development in Minahasa Regency: Challenges and Policy Implementation in Education, Health, and Workforce Sectors - Dondokambey, Robby; Katuuk, Deitje A.; Rawis, Joulanda A M; Lengkong, Jeffry Sony Junus; Umbase, Ruth (International Journal of Information Technology and Education, 2025)
This study investigates the quality of Human Resource Development (HRD) in Minahasa Regency, Indonesia, focusing on the interrelated dimensions of education, health, and economic welfare within the context of local governance. A qualitative descriptive design was employed, with data collected through interviews, field observations, and document analysis across 25 districts. The findings reveal that despite the steady improvement of the Human Development Index (HDI), significant disparities remain in access to education, healthcare services, skilled labor distribution, and digital infrastructure. The study identifies key challenges, including fragmented inter-agency coordination, limited budgetary support, and a persistent mismatch between educational outcomes and labor market demands. In addition, weaknesses in existing monitoring and evaluation systems were found to constrain evidence-based policymaking and program effectiveness. This research proposes strategic measures to strengthen HRD governance, such as enhancing cross-sector collaboration, optimizing resource allocation, expanding vocational and technology-oriented training, and developing integrated monitoring mechanisms. The study contributes to the literature on regional HRD by offering an empirical and contextualized framework for improving human capital development in decentralized governance settings and emerging regions.